(X+43)+(2x-73)=180

Simple and best practice solution for (X+43)+(2x-73)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+43)+(2x-73)=180 equation:


Simplifying
(X + 43) + (2x + -73) = 180

Reorder the terms:
(43 + X) + (2x + -73) = 180

Remove parenthesis around (43 + X)
43 + X + (2x + -73) = 180

Reorder the terms:
43 + X + (-73 + 2x) = 180

Remove parenthesis around (-73 + 2x)
43 + X + -73 + 2x = 180

Reorder the terms:
43 + -73 + X + 2x = 180

Combine like terms: 43 + -73 = -30
-30 + X + 2x = 180

Solving
-30 + X + 2x = 180

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + X + 30 + 2x = 180 + 30

Reorder the terms:
-30 + 30 + X + 2x = 180 + 30

Combine like terms: -30 + 30 = 0
0 + X + 2x = 180 + 30
X + 2x = 180 + 30

Combine like terms: 180 + 30 = 210
X + 2x = 210

Add '-2x' to each side of the equation.
X + 2x + -2x = 210 + -2x

Combine like terms: 2x + -2x = 0
X + 0 = 210 + -2x
X = 210 + -2x

Simplifying
X = 210 + -2x

See similar equations:

| (7q-7)+(5q-9)= | | 6x+1=3(2x+1)-x+8 | | x+-5y=-3 | | 10x^2-45x-25=0 | | X+11=5x-2 | | -64-(4x-14)=15 | | b+10=96 | | 6x+3+39=90 | | 4x-4x=-6 | | 7(x-6)=4 | | 8x+4=6x-4 | | X=-6-11 | | 70x+55b=14 | | 6(x+3)-(x+2)=27 | | -x+3+13x=-6+3x+54 | | 18y=9y+18 | | 5(x-4)+4(x-6)=7 | | 2-x+5=7-3 | | 5x+4+26=90 | | -x+2+7x=-2+2x+16 | | N^2+6n-21=0 | | 5m-4=2m-22 | | 22x+22(x-9)=45 | | 6v+2v+3= | | x^4+72x^2+94400=0 | | 2(4)+p=35 | | -16t(t+1)(t-5)=0 | | 2x+4(x-5)=2(x-4) | | 8m-11+2m-4=180 | | -x+3+14x=-6+4x+36 | | 2x+6-x-3=40 | | 0.09x+0.19(x+7000)=3570 |

Equations solver categories